2020
DOI: 10.1057/s41287-020-00333-5
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modelling of COVID-19 Death Risk in India in the Early Phase of the Pandemic

Abstract: We improve upon the modelling of India’s pandemic vulnerability. Our model is multidisciplinary and recognises the nested levels of the epidemic. We create a model of the risk of severe COVID-19 and death, instead of a model of transmission. Our model allows for socio-demographic-group differentials in risk, obesity and underweight people, morbidity status and other conditioning regional and lifestyle factors. We build a hierarchical multilevel model of severe COVID-19 cases, using three different data sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…17 We have also found some positive association between CSR or DCSR and multi-morbidity for monthly data, but not weekly data. The estimated coefficient varies across different models, but, for instance, based on Column 4 on CSR, we observe that a 1% increase in urbanization is associated with a 0.36% increase in CSR as consistent with Das et al (2021) and Olsen et al (2020). As expected, we find that the share of those among the elderly with multi-morbidity conditions is positively associated with DCSR or CSR (e.g., a 1% increase in the share is correlated with a 0.54%-0.67% increase in CSR, Columns 3 and 5).…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…17 We have also found some positive association between CSR or DCSR and multi-morbidity for monthly data, but not weekly data. The estimated coefficient varies across different models, but, for instance, based on Column 4 on CSR, we observe that a 1% increase in urbanization is associated with a 0.36% increase in CSR as consistent with Das et al (2021) and Olsen et al (2020). As expected, we find that the share of those among the elderly with multi-morbidity conditions is positively associated with DCSR or CSR (e.g., a 1% increase in the share is correlated with a 0.54%-0.67% increase in CSR, Columns 3 and 5).…”
Section: Resultsmentioning
confidence: 67%
“…The authors found that among the eight states that have contributed to over 80% of the confirmed COVID-19 cases in India, as of June 17, 2020, five states had a high vulnerability index value and the remaining three had medium vulnerability (e.g., Maharashtra with 33% of the total COVID cases and the vulnerability index 0.829, the seventh from the bottom). Although Acharya and Porwal have not estimated the vulnerability index using the actual COVID-19 data, their analysis implied the importance of socioeconomic factors, which is consistent with Olsen et al (2020).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Olsen et al. (2020) estimated the pandemic vulnerability in the early phase in India using a hierarchical model accounting for social/demographic/group differentials among impact factors. Chen et al.…”
Section: Methodsmentioning
confidence: 99%